The Batrisini of Tibet: unveiling an enigmatic ant-loving beetle diversity at Earth’s “Third Pole” (Coleoptera, Staphylinidae, Pselaphinae) - Yin, Zi-Wei (Zootaxa, 2022)
The taxonomic knowledge of the pselaphine tribe Batrisini (Coleoptera: Staphylinidae) from the Tibet Autonomous Region is summarized, with 80 species placed in 13 genera. Two genera and 68 species are described as new, aided with illustrations of habitus and diagnostic characters: Arthromelodes alpitorus sp. nov., A. angulatus sp. nov., A. aniqiao sp. nov., A. bicolor sp. nov., A. complexus sp. nov., A. cona sp. nov., A. crassicornis sp. nov., A. criniger sp. nov., A. cylindricus sp. nov., A. flosculus sp. nov., A. gyamda sp. nov., A. intricatus sp. nov., A. lage sp. nov., A. langjicuo sp. nov., A. latithorax sp. nov., A. lebus sp. nov., A. lotus sp. nov., A. markam sp. nov., A. monba sp. nov., A. nepaeformis sp. nov., A. nomurai sp. nov., A. songxiaobini sp. nov., A. speciosus sp. nov., A. torus sp. nov., A. zhangmu sp. nov., A. zhentangensis sp. nov., Batriscenaulax campestris sp. nov., Batrisiella acclivis sp. nov., Batrisiella beibeng sp. nov., Batrisiella bomea sp. nov., Batrisiella concisa sp. nov., Batrisiella curvitibialis sp. nov., Batrisiella ganma sp. nov., Batrisiella guttata sp. nov., Batrisiella zhujianqingi sp. nov., Batrisodes guoguotang sp. nov., Batrisodes hanmi sp. nov., Coryphomimus levigatus gen. et sp. nov., Coryphomodes budda sp. nov., Coryphomodes cephalicus sp. nov., Coryphomodes chenzhilini sp. nov., Gyrongita uniformis gen. et sp. nov., Sathytes aequalis sp. nov., S. asura sp. nov., S. caichenyangi sp. nov., S. dawai sp. nov., S. duojii sp. nov., S. laticornis sp. nov., S. pengzhongi sp. nov., S. proclivis sp. nov., S. pseudograndis sp. nov., S. sympatricus sp. nov., S. virupaksa sp. nov., S. yigongensis sp. nov., Tribasodites bari sp. nov., T. cellulanus sp. nov., T. constrictus sp. nov., T. dilophus sp. nov., T. elongatus sp. nov., T. grandiceps sp. nov., T. gyirong sp. nov., T. kiypu sp. nov., T. mirabilis sp. nov., T. prolixicornis sp. nov., T. pugiunculus sp. nov., T. vertexalis sp. nov., T. yatung sp. nov., and Trisinus quadrilobus sp. nov. The genus Plocamarthrus Jeannel, 1960 is proposed as a subjective junior synonym of Arthromelodes Jeannel 1954, syn. nov., resulting in Arthromelodes championi (Jeannel, 1960) comb. nov. (type species of Plocamarthrus), A. cameroni (Jeannel, 1960) comb. nov., A. planiceps (Jeannel, 1960) comb. nov., and A. abdominalis (Jeannel, 1960) comb. nov. Arthromelodes championi and Sathytes simplex Löbl, 1979 are reported to occur in Tibet, which are also new country records for China. Additional collecting data are provided for Hingstoniella lata Jeannel, 1960, Sathytes panzhaohuii Yin & Shen, 2020, Sathytes transversus Yin & Shen, 2020, and Sathytes xizangensis Yin & Shen, 2020. Keys for identification of the genera and species are presented. Maps showing the distribution of each species are provided, supplemented with habitat photos. Lists of Tibetan species of Batrisini and of other pselaphine groups are given, adding up to 95 species.